Impacts of Openness to Experience on Learning Innovation Model The Moderating Effect of Teacher Knowledge-Sharing - Ghafar, Muhammad; Zarkasyi, Ahmad; Adam, Faisol Mahmud (IAIN Ponorogo, 2022)
This study aims to determine the openness to experience and knowledge sharing on certified teacher learning innovations in Banyuwangi. This research was non-experimental quantitative research with a survey design. A total of 110 public and private Madrasah Aliyah teachers in Banyuwangi selected by purposive sampling participated in this survey research. The collected data were then analyzed using the WARP PLS 7.0 application and the IBM Statistical Package for Social Science (SPSS) version 23. Using WARP PLS 7.0 found that: 1) openness to experience affected knowledge sharing by 77 and 3%2) openness to experience affected the innovative learning model by 48.0%. 3) knowledge sharing affects the innovative learning model by 40.6%. 4) openness to experience the innovation learning model through knowledge sharing is 13.5. It shows that openness to experience in the form of ideas through the desire to be creative with the ideas and ideas that teachers have in various madrasa activities has an impact on the active attitude of teachers in writing books, articles, or research to share their knowledge with other teacher colleagues so that teachers have habituation which is indicated by learning patterns that are developed more effectively and efficiently.